CDR132L improves systolic and diastolic function in a large animal model of chronic heart failure. (22nd October 2020) - Batkai, Sandor; Genschel, Celina; Viereck, Janika; Rump, Steffen; Bär, Christian; Borchert, Tobias; Traxler, Denise; Riesenhuber, Martin; Spannbauer, Andreas; Lukovic, Dominika; Zlabinger, Katrin; Hašimbegović, Ena; et al.
Abstract: Aims: Cardiac miR-132 activation leads to adverse remodelling and pathological hypertrophy. CDR132L is a synthetic lead-optimized oligonucleotide inhibitor with proven preclinical efficacy and safety in heart failure (HF) early after myocardial infarction (MI), and recently completed clinical evaluation in a Phase 1b study (NCT04045405). The aim of the current study was to assess safety and efficacy of CDR132L in a clinically relevant large animal (pig) model of chronic heart failure following MI. Methods and results: In a chronic model of post-MI HF, slow-growing pigs underwent 90 min left anterior descending artery occlusion followed by reperfusion. Animals were randomized and treatment started 1-month post-MI. Monthly intravenous (IV) treatments of CDR132L over 3 or 5 months (3× or 5×) were applied in a blinded randomized placebo-controlled fashion. Efficacy was evaluated based on serial magnetic resonance imaging, haemodynamic, and biomarker analyses. The treatment regime provided sufficient tissue exposure and CDR132L was well tolerated. Overall, CDR132L treatment significantly improved cardiac function and reversed cardiac remodelling. In addition to the systolic recovery, diastolic function was also ameliorated in this chronic model of HF. Conclusion: Monthly repeated dosing of CDR132L is safe and adequate to provide clinically relevant exposure and therapeutic efficacy in a model of chronic post-MI HF. CDR132L thus should be explored as treatment for the broad area of chronic heart failure. Graphical Abstract: